Analisis Modifikasi Visual Gerakan Pencak Silat Melalui Teknik Gerakan Kamera Pada Film The Raid 2 - Iklima Nur Mufida; Yully Ambarsih Ekawardhani (Universitas Komputer Indonesia, 2022)
The purpose of this study is to find the visual modifications of Pencak silat movements in The Raid 2 movie through camera movement techniques. The martial arts movements used in The Raid 2 movie have been modified according to the needs of the movie. A descriptive qualitative method was used to collect and process data and information that was needed for this research. The author of this research also did a visual analysis of the Pencak silat movements that were shown in several selected scenes. The analysis was carried out by choosing several scenes from The Raid 2 movie and analyzing the camera movement techniques such as tilting, following, and panning in the selected scenes. The results of this study indicate that in The Raid 2 movie, there are Pencak silat movements that have been modified according to the needs of the film that was analyzed from camera movement techniques. And this research can describe how the original movement has been modified according to the interests of a film. This research also found that the Pencak silat movements modification as the result of mixing traditional martial arts and modern movie technology raises the interest of the audience.